Development of a High Performance Liquid Chromatographic Assay Measuring Mezlocillin in Serum or Tissue. Issue 1 (1993) - Mya, Sandra; Gain, Ron E.; Larsen, Bryan
Abstract : Objective: This study evaluated the blood and uterine tissue concentration of mezlocillin, a broadspectrum penicillin. Methods: We adapted a liquid chromatographic method to measure mezlocillin in serum and tissue. Mezlocillin reference standard was diluted in water, chromatographed on a reversed phase C18 column eluted at 1.5 ml/min with acetonitrile and phosphate buffer (1:3 v:v), and detected spectrophotometrically at 210 nm. Mezlocillin was administered to 14 premenopausal women scheduled to undergo vaginal hysterectomy. Each patient received a 4 g IV infusion of the drug 30 to 60 min prior to surgery. During surgery, tissue was removed from the uterine cervix and blood was obtained for assay of mezlocillin content. Results: Chromatography of the mezlocillin standard furnished a discrete peak with a retention time of 2.4 min. The sensitivity of the assay was 0.1 µg/ml with a linear response up to 100 µg/ml. The correlation coefficient for the standard curve was 0.9997. When reference standard was diluted in pooled human serum, the assay was complicated by interfering compounds. These were removed by ether extraction. The sensitivity of the assay performed in serum was 3 µg/ml. Serum samples contained from 81.2 to 358 µg of mezlocillin/ml with an average serum concentration of 207.5 µg/ml. When serum containing a known amount of mezlocillin was homogenized for a period of time similar to that required to homogenize tissue samples, a deteatable loss of drug was observed and was applied as a correction factor to the measured tisulevels. After correction, the average tissue level was 117.2 µg/ml and ranged from 27% to 98% of the serum levels. Conclusions: The serum concentration of mezlocillin after IV infusion of 4 g was greater than that required to inhibit the majority of the most significant organisms responsible for post-hysterectomy sepsis. Although tissue levels appeared to be consistently lower than serum levels, they could be expected to provide an inhibitory effect against many of the bacterial strains that contaminate the surgical site.